2007
DOI: 10.1002/pen.20821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fracture behavior of multilayered polypropylene sheets obtained by coextrusion

Abstract: The mechanical and fracture behavior of multilayered sheets (up to three layers) is presented. The sheets were processed by plane coextrusion-calendering using two polypropylene-based materials, isotactic polypropylene homopolymer (H0), and an ethylene-propylene block copolymer (C1) with 5.5% ethylene content in weight. Combining these materials five different sheets were produced, (H0, C1, H0-C1, H0-C1-H0, and C1-H0-C1), with an overall thickness of 0.5 mm. The processing variables (temperature, extrusion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Similar fracture behaviors were observed for all of the extrusion sheets. The fracture behaviors were strongly dependent on the testing direction …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar fracture behaviors were observed for all of the extrusion sheets. The fracture behaviors were strongly dependent on the testing direction …”
Section: Resultsmentioning
confidence: 99%
“…Compared with common structure, the layered structure has better mechanical properties. Simulation results obtained by some theoretical models, such as the equivalent box, have indicated that the mechanical properties, including the modulus, yield strength, and tensile strength, of layered structure are higher than those of a dispersed, cocontinuous structure . Kolarik ascribed this enhancement in the mechanical properties of a layered morphology to its best phase continuity in the direction of the acting force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to best phase continuity of multilayered structure, the mechanical properties, including the modulus, yield strength, and tensile strength, of multilayered structure are higher than those of conventional structure. [31][32][33] Consequently, the puncture strength, which seriously depends on the modulus, yield strength, and tensile strength, for multilayered structure were higher than that for blend sample. 27 And the puncture strengths of multilayered and blend samples were both decreased with the volume fraction of POE increasing, indicating a lower deformation resistance of puncture.…”
Section: Puncture Behaviorsmentioning
confidence: 91%